Bioactive Earthworm Peptides Produced by Novel Protease-Producing Bacillus velezensis PM 35 and Its Bioactivities on Liver Cancer Cell Death via Apoptosis, Antioxidant Activity, Protection Against Oxidative Stress, and Immune Cell Activation - Wasunan, Pimphan; Maneewong, Chutamas; Daengprok, Wichittra; Thirabunyanon, Mongkol (Frontiers in Microbiology, 2022)
Earthworms have long been used as traditional medicine. The purposes of this research were to create bioactive peptide from the unique Amynthas arenulus earthworm (PAAE) and test their potentials on liver cancer bioprophylactic activity, antioxidant, oxidative stress protection, and immune cell activation. This earthworm had a high protein content ratio, at 55.39%. Besides, PM 35 is one out of 58 bacterial isolates that exhibited the highest protease and yield protein production which was chosen as the protease-producing bacteria to hydrolyze the protein. The genera were identified by 16S rRNA and 16S–23S rRNA comparison and confirmed as Bacillus velezensis PM 35. The response surface methodology was applied to optimize these hydrolysis parameters i.e., the enzyme/substrate (E/S) concentration ratio (1-3% (v/v)) and time (1-3 h) of the hydrolyzing earthworm’s proteins. The optimal hydrolyzing conditions were 3% (v/v) of E/S concentration ratio and 3 h of hydrolysis time, which found protein-hydrolysate yield (24.62%), and degree of hydrolysis (85.45%) as the highest. After being challenged in the gastrointestinal tract resistant model, these PAAEs (MW < 3 kDa, and MW 3-5 kDa) induced liver cancer cell (HepG2) death via apoptotic action modes (cell morphological change and DNA fragmentation). The PAAEs (MW <3 kDa) exhibited significant antioxidant activity via DPPH, ABTS, and FRAP with IC50 values of 0.94, 0.44, and 6.34 mg/mL, respectively. The PAAEs (MW < 3 kDa) were non-cytotoxic and protected the mouse fibroblast cells (L929) against oxidative stress. These PAAEs (MW < 3kDa, 0.2 mg/mL) stimulated the B lymphocytes (122.3%), and T lymphocytes (126.7%) proliferation. This research suggests that PAAEs can be used in a variety of applications, especially in the food and pharmaceutical industries.